PENINGKATAN KETRAMPILAN IBU – IBU RUMAH TANGGA MELALUI PELATIHAN PRODUK KERAJINAN YANG MENGGUNAKAN DASAR KAIN YANG MEMPUNYAI NILAI TAMBAH DALAM RANGKA MENINGKATKAN PENDAPATAN KELUARGA - Efni, Yulia; Hendriani, Susi; Atami, Aulia Pinto (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2025)
The development of the creative economy in Indonesia is increasing in line with the use of various information technologies that are increasingly supportive and widely implemented by MSMEs, the majority of which are run by housewives. Housewives have the potential to produce valuable products that can be sold to supplement family income. Valuable products can be created from unused materials, and it is essential for housewives to have the knowledge and skills to identify and capitalize on opportunities within the creative industry. Therefore, training/counseling sessions are necessary. The training activities were conducted for housewives in Labuhbaru Timur Village, Payung Sekaki Subdistrict, Pekanbaru City. The results of the activity showed an increase in housewives' understanding that valuable products can be produced from materials considered worthless and the opportunities that can be achieved through the creative economy. Abstract: